Enhancing Telework: Public Sector Employees’ Attitudes and Key Factors for Effective Implementation - Xanthopoulou, Panagiota; Vyttas, Vassilis; Gaitanarou, Afroditi (International Conference on Business and Economics - Hellenic Open University, 2025)
Teleworking is a working model that has experienced a substantial increase in recent years at a global level due to the emergence of the COVID-19 pandemic. This study aims to identify employees’ attitudes in the public sector regarding the implementation of telework, as well as the recording of the characteristics that contribute to improving performance and, therefore, its more effective implementation. A bibliographic review method was chosen where a total of 46 empirical studies or primary data were studied, both in Greek and foreign language literature. From the literature review results, it was found that those employed in the public sector maintain a positive attitude towards the implementation of telework, provided that appropriate working conditions are ensured, and their expectations are met. Also, it was observed that the existence of the necessary infrastructure, the attitudes of the employees, the provision of suitable working conditions, as well as the existence of the required knowledge and skills are the factors that influence the effectiveness of the implementation of telework. Finally, it is proposed that empirical research be carried out in Greece due to the need for corresponding studies. JEL Classifications: J24, J38, J28, J45 Keywords: telework, public sector, employee attitudes, telework effectiveness, job satisfaction